UNIKNYA KURIKULUM PENDIDIKAN YANG ADA DI INDONESIA - Yusri; Babang Robandi; Dedeh Kurniasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The history of the formation of the education curriculum in Indonesia reflects a long journey influenced by various social, political and cultural factors. Various kinds of curricula have been born in Indonesia, including the Colonial Period curriculum, the Independence Period, the 1947 and 1952 Curriculum, the 1968 Curriculum, the Competency Based Curriculum (2004), the 2013 Curriculum, and finally the Independent Curriculum. Overall, the uniqueness of the curriculum in Indonesia reflects efforts to create a relevant and adaptive education system, although it still requires improvements and adjustments to achieve better educational goals in the future. The educational curriculum in Indonesia has unique characteristics that differentiate it from other countries. This system reflects cultural values, religion and a strong national spirit, and continues to develop according to the needs of the times. With a variety of cultures, languages ​​and traditions, this curriculum is designed to reflect the diversity and needs of Indonesian society. However, behind its uniqueness, there are challenges and opportunities that need to be understood more deeply. In this article, we will discuss the unique characteristics of the education curriculum in Indonesia according to experts, both from within the country and abroad.